Le périple en Albanie d’un « Malgré-nous » mosellan - Évelyne Noygues (Cahiers Balkaniques)
From Alsace-Lorraine, incorporated by force into the German Army, this “Malgré-nous” organized and made a success of his evasion, while he had followed Wehrmacht to Albania, to join the Albanian National Army. Called “Jean the French patriot of the XXIIth Brigade”, he participated in the fights against the German soldiers, near the capital in central Albania and in the North of the country.The Second World War generated enormous sufferings and, sometimes, original situations too, as the one that Jean Dutzer lived, while he was not 20 years old.